The Effect of Digitalization on Employee Work Effectiveness at PT. Ramayana Lestari Sentosa Tbk Semper Branch - Serli, Serli; Fa’uzobihi, Fa’uzobihi; Imanuddin, Kaffah (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The aim of this research is to determine the effect of digitalization on the work effectiveness of PT employees. Ramayana Lestari Sentosa, Tbk Semper Branch. This research uses a quantitative descriptive method with data collection techniques through distributing questionnaires and library data. In this research, the saturated sampling method used was 48 employees of PT. Ramayana Lestari Sentosa, Tbk Semper Branch, using simple linear regression data analysis techniques. The results of this research show that there is an influence between digitalization on the work effectiveness of employees at PT. Ramayana Lestari Sentosa, Tbk Semper Branch has a strong positive influence and has a contribution of 65% to the employee work effectiveness variable. It is hoped that the results of this research will contribute to further research.